2021
DOI: 10.1177/08830738211012804
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of SGS-742, a γ-aminobutyric acid B (GABA-B) Receptor Antagonist, for Succinic Semialdehyde Dehydrogenase Deficiency

Abstract: We examined safety, tolerability, and efficacy of SGS-742, a γ-aminobutyric acid B (GABA-B) receptor antagonist, in patients with succinic semialdehyde dehydrogenase deficiency. This was a single-center randomized, double-blind crossover phase II clinical trial of SGS-742 versus placebo in patients with succinic semialdehyde dehydrogenase deficiency. Procedures included transcranial magnetic stimulation and the Adaptive Behavior Assessment Scale. Nineteen subjects were consented and enrolled; the mean age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Importantly, these treatment strategies produced appreciable therapeutic outcomes in aldh5a1 −/− mice including seizure suppression, phenotypic reversal and extended lifespan. These promising preclinical results also formed the scientific basis for clinical drug trials, including taurine [ 37 , 38 ] and a recently completed study of GABA B R antagonist SGS-742 [ 39 ]. Yet, while these drugs were well-tolerated in patients, their therapeutic effects were rather limited.…”
Section: A Brief History and Update On Ssadhd Researchmentioning
confidence: 99%
“…Importantly, these treatment strategies produced appreciable therapeutic outcomes in aldh5a1 −/− mice including seizure suppression, phenotypic reversal and extended lifespan. These promising preclinical results also formed the scientific basis for clinical drug trials, including taurine [ 37 , 38 ] and a recently completed study of GABA B R antagonist SGS-742 [ 39 ]. Yet, while these drugs were well-tolerated in patients, their therapeutic effects were rather limited.…”
Section: A Brief History and Update On Ssadhd Researchmentioning
confidence: 99%
“…109 Current treatment options for SSADHD are symptomatic with limited efficacy. 110 Gene replacement therapy is a potential disease-modifying treatment for SSADHD but is currently unavailable. 111,112 The broad expression profile of ALDH5A1 in the brain suggests that a brainwide-targeted approach is likely necessary.…”
Section: Clinical Background and Preclinical Considerations For Gene ...mentioning
confidence: 99%
“…An SSADHD natural history study is ongoing, and thus far revealed a 15% incidence of sudden unexpected death in epilepsy in this patient population among other developmental and behavioral morbidities 109 . Current treatment options for SSADHD are symptomatic with limited efficacy 110 . Gene replacement therapy is a potential disease‐modifying treatment for SSADHD but is currently unavailable 111,112 .…”
Section: Current Progress In Developing Gene Replacement Therapy For ...mentioning
confidence: 99%
“…For example, the only phase II clinical trial to date, which tested the GABA B receptor antagonist SGS-742, neither showed any improvement of cognition nor of cortical excitability. 7 A more detailed understanding of the pathophysiology of the disease, beyond the accumulation of GABA and GHB, may support novel therapy development for SSADHD. Whereas the deficiency directly affects GABA metabolism, it is possible that related metabolic pathways are affected as well.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical trials (phase I or II) have been performed, but without beneficial outcomes. For example, the only phase II clinical trial to date, which tested the GABA B receptor antagonist SGS‐742, neither showed any improvement of cognition nor of cortical excitability 7 …”
Section: Introductionmentioning
confidence: 99%